IRG1 and Inducible Nitric Oxide Synthase Act Redundantly with Other Interferon-Gamma-Induced Factors To Restrict Intracellular Replication of Legionella pneumophila - Jordan V. Price (American Society for Microbiology, 2019)
ABSTRACT Interferon gamma (IFN-γ) restricts the intracellular replication of many pathogens, but the mechanism by which IFN-γ confers cell-intrinsic pathogen resistance remains unclear. For example, intracellular replication of the bacterial pathogen Legionella pneumophila in macrophages is potently curtailed by IFN-γ. However, consistent with prior studies, no individual genetic deficiency that we tested completely abolished IFN-γ-mediated control. Intriguingly, we observed that the glycolysis inhibitor 2-deoxyglucose (2DG) partially rescued L. pneumophila replication in IFN-γ-treated macrophages. 2DG inhibits glycolysis and triggers the unfolded protein response, but unexpectedly, it appears these effects are not responsible for perturbing the antimicrobial activity of IFN-γ. Instead, we found that 2DG rescues bacterial replication by inhibiting the expression of two key antimicrobial factors, inducible nitric oxide synthase (iNOS) and immune-responsive gene 1 (IRG1). Using immortalized and primary macrophages deficient in iNOS and IRG1, we confirmed that loss of both iNOS and IRG1, but not individual deficiency in either gene, partially reduced IFN-γ-mediated restriction of L. pneumophila. Further, using a combinatorial CRISPR/Cas9 mutagenesis approach, we found that mutation of iNOS and IRG1 in combination with four other genes (CASP11, IRGM1, IRGM3, and NOX2) resulted in a total loss of L. pneumophila restriction by IFN-γ in primary bone marrow macrophages. Our study defines a complete set of cell-intrinsic factors required for IFN-γ-mediated restriction of an intracellular bacterial pathogen and highlights the combinatorial strategy used by hosts to block bacterial replication in macrophages. IMPORTANCE Legionella pneumophila is one example among many species of pathogenic bacteria that replicate within mammalian macrophages during infection. The immune signaling factor interferon gamma (IFN-γ) blocks L. pneumophila replication in macrophages and is an essential component of the immune response to L. pneumophila and other intracellular pathogens. However, to date, no study has identified the exact molecular factors induced by IFN-γ that are required for its activity. We generated macrophages lacking different combinations of IFN-γ-induced genes in an attempt to find a genetic background in which there is a complete loss of IFN-γ-mediated restriction of L. pneumophila. We identified six genes that comprise the totality of the IFN-γ-dependent restriction of L. pneumophila replication in macrophages. Our results clarify the molecular basis underlying the potent effects of IFN-γ and highlight how redundancy downstream of IFN-γ is key to prevent exploitation of macrophages by pathogens.